The Implementation Problem Based Learning to Enhance Activity and Students Learning Outcome - Sari, Melinda Ratna (Unversitas Negeri Malang, 2018)
Based on a preliminary observation made in SMA Negeri Pasirian in the tenth-grade students of Social Studies 3, it is known that the process of learning on the economy is still using a model that has not been easy making students become excited and active which adversely affects the learning activities and student learning outcomes. Observation result also showed that the tenth grade students of Social Studies 3 has an average score of Economic lessons is less good than other the tenth grade students of Social Studies but the thoroughness of the result of the tenth grade students of Social Studies 3 was <75% of the specified standard passing grade, in addition to the lack of liveliness the tenth grade students of Social Studies 3 also a problem in learning activities in the classroom that need a proper learning, interesting, and fun in form of problem based learning model which is expected to help students to hone their thinking towards a problem so as to increase the activity of learning as well as students learning outcomes. Based on the survey result, it revealed that there is an increased activity the tenth-grade students of Social Studies 3. This is indicated by the percentage of students activity by 69,4% the first cycle and the second first cycle increased to be 87,1%. Improving student learning outcomes can be seen from the result of students mastery of cognitive with the average post-test value of students increased from the first cycle of 65,63% rising to 82,2% in the second cycle.Keywords:Â Problem Based Learning, Liveliness, and Students Learning Outcomes